Measure the degree of availability of the learning organization’s dimensions and their applications at Fakeeh College for Medical Sciences - Filali, Najla Adnan; Aezam, Salwa Hassan Farid (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to measure the degree of availability of the learning organization’s dimensions and their applications in Fakeeh College for Medical Sciences, by identifying the degree of availability of the learning organization’s dimensions, identifying the areas of application of the concept of the organization, and identifying the obstacles to implementing the concept of the learning organization at Fakih College of Medical Sciences from the respondents ’viewpoint. and to achieve this goal the researcher used the descriptive-analytical approach. She prepared a questionnaire and was distributed to a randomly selected sample, consisting of (100) administrators and faculty members, in the College Fakih for Medical Sciences, and the arithmetic averages and standard deviations were used, and the study concluded with a set of results, the most important of which are: There are three dimensions for the learning organization at Fakeeh College for Medical Sciences from the point of view of its employees to a large degree, namely (level of learning, empowerment of workers, level of technology application). While there are two dimensions for the learning organization in the Fakeeh College for Medical Sciences with a medium degree, they are (the organization's environment, the level of knowledge management). The study recommended that learning be taken care of at all levels and including it within the training programs to acquire its various skills, and to establish an effective methodology for knowledge management that includes knowledge activities such as (finding and acquiring and storage, transfer, retrieval and application of knowledge), and work to increase the cognitive skills of workers, through communication with various Saudi academic organizations Develop their cognitive abilities.
Keywords: Dimensions of the learning organization and its applications; Fakih College of Medical Sciences; Kingdom of Saudi Arabia